Joint decision making in a mental health rehabilitation community: The impact of support workers' proposal design on client responsiveness. Issue 1 (2nd January 2022) - Stevanovic, Melisa; Valkeapää, Taina; Weiste, Elina; Lindholm, Camilla
ABSTRACT: Using both statistical methods and conversation analysis, we examined how support workers in a mental health rehabilitation community encourage clients to participate in joint decision-making processes. Drawing on video-recordings of 29 community meetings as data, we considered support workers' proposals (N = 449) and clients' responsiveness to them. Support workers' proposals were coded for their linguistic and other features and clients' responsiveness was assessed by three independent raters. Multiple linear regression (MLR) analysis was carried out. A significant regression equation with seven predictor variables accounted for 24% of the variance in the data. Four variables predicted a higher level of client responsiveness: the use of explicit recipient address term, "quasi-open" proposal form, support worker's long work experience, and the average level of client participation during a session. Three variables predicted a lower level of client responsiveness: grammatical complexity of proposal form, modal declarative proposal form, and the presence of only one support worker in a session. The qualitative conversation-analytic investigation highlighted the advantages of the careful fine-tuning of openness vs. closedness of proposal form, the reflexive awareness of which, we argue, may help mental health professionals to encourage clients' responsiveness in joint decision-making processes and thereby their participation in communal life.